Microwave Modification of N-Doped Carbon for High Performance Lithium-Ion Batteries. Issue 14 (12th December 2017) - Meng, Yanshuang; Xiao, Mingjun; Wang, Lei; Duan, Chaoyu; Zhu, Fuliang; Zhang, Yue
Abstract : In this work, the modification effect of microwave irradiation on the surface functional groups and electrochemical properties of N-doped carbon (NDC) was investigated. The microwave irradiation generated a large number of edge defects and thus many pyridinic and pyrrolic N on the surface of NDC, which served as the active sites for Li + ions adsorption. The microwave irradiation also led to the decomposition of the hydroxyl functional groups on the surface of NDC, which were beneficial to the formation of a more stable and conductive solid electrolyte interface (SEI) film on the surface of NDC. Therefore, the microwave modified NDC delivered a high specific capacity of 613.5 mAh g −1 after 50 cycles at 0.1 C and excellent rate performance when used as anode material of lithium ion battery.